2013
DOI: 10.1002/jrs.4338
|View full text |Cite
|
Sign up to set email alerts
|

Laser wavelength dependence of background fluorescence in Raman spectroscopic analysis of synovial fluid from symptomatic joints

Abstract: Gout is a disease process where the nucleation and growth of crystals in the synovial fluid of joints elicit painful arthritis-like symptoms. Raman spectroscopy is evolving as a potential diagnostic tool in identifying such crystals; however, attainment of sufficient Raman signal while overcoming the background fluorescence remains as a major challenge. The current study focused on assessing whether excitation in 532–700 nm range will provide greater signal intensity than the standard 785 nm while not being im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…The process eliminates subjectivity in the diagnosis of gout, an advantage over the PLM-based diagnosis which is operator dependent 28 . Previously we reported that the fluorescence spectra of raw and digested synovial samples to be comparable, indicating that digestion did not increase the background fluorescence 29 . Although filtration had discarded the organic material from the synovial fluid and digestive enzymes, there was residual organic matter in the crystals deposit, leading to background fluorescence in the Raman spectra.…”
Section: Discussionmentioning
confidence: 61%
“…The process eliminates subjectivity in the diagnosis of gout, an advantage over the PLM-based diagnosis which is operator dependent 28 . Previously we reported that the fluorescence spectra of raw and digested synovial samples to be comparable, indicating that digestion did not increase the background fluorescence 29 . Although filtration had discarded the organic material from the synovial fluid and digestive enzymes, there was residual organic matter in the crystals deposit, leading to background fluorescence in the Raman spectra.…”
Section: Discussionmentioning
confidence: 61%
“…However at 532 nm excitation, significant levels of fluorescence may be present hindering the Raman signal. This problem can be solved by using higher wavelength (785 nm excitation) laser which avoids fluorescence and still produces sufficient Raman signal …”
Section: Raman Spectroscopy Analysismentioning
confidence: 99%
“…Thus, Raman spectra obtained with 633 and 532 nm were interfered by different fluorescence background, leading to small weak peaks. Although the Raman shift showed negligible variations with these lasers (785, 633, and 532 nm), the fluorescence noise changed with the alteration of laser and most fluorescence interference could be avoided by the laser at 785 nm . The results pointed out that 785‐nm laser was more appropriate for spectrum collection of the samples in this study.…”
Section: Resultsmentioning
confidence: 71%